10.47313 Melanggengkan Patriarki: Pembingkaian Media terhadap Kasus Perundungan Perempuan dalam Wacana Berita Digital - Anggraini, Indrani Dewi; Sarah, Nani Nuraini (Pujangga, 2025)
Abstract News about the bullying of women is a serious issue that affects the emotional and psychological well-being of victims and can even lead to tragic deaths. However, media coverage is not always objective due to biases in how news is structured and presented. The media frames these cases by emphasizing certain aspects through word choice, narratives, visuals, and perspectives that shape audience understanding. Bias in news framing can influence public opinion and reinforce gender stereotypes. This study analyzes six news reports on the bullying of women in the digital media platform detik.com in 2024 using a qualitative descriptive method and a critical discourse analysis approach based on content analysis. Utilizing Sara Mills' theory, the analysis focuses on three aspects: subject-object positioning, gender roles, and socio-cultural context. The media often reinforces patriarchal dominance by portraying women as passive objects while men are positioned as dominant subjects who control the narrative. This representation reflects the structure of patriarchal power in society, where men have greater control over social discourse, including in the media. As a result, gender inequality continues to be reproduced, positioning women as victims who lose their agency and weakening their ability to confront bullying. Keywords: framing, gender, bullying, digital mass media.